Django RESTful web services the easiest way to build Python RESTful APIs and web services with Django - Hillar, Gastón C. (Packt Publishing, 2018)
Django is a Python web framework that makes the web development process very easy. It reduces the amount of trivial code, which simplifies the creation of web applications and results in faster development. It is very powerful and a great choice for creating RESTful web services. If you are a Python developer and want to efficiently create RESTful web services with Django for your apps, then this is the right book for you. The book starts off by showing you how to install and configure the environment, required software, and tools to create RESTful web services with Django and the Django REST framework. We then move on to working with advanced serialization and migrations to interact with SQLite and non-SQL data sources. We will use the features included in the Django REST framework to improve our simple web service. Further, we will create API views to process diverse HTTP requests on objects, go through relationships and hyperlinked API management, and then discover the necessary steps to include security and permissions related to data models and APIs. We will also apply throttling rules and run tests to check that versioning works as expected. Next we will run automated tests to improve code coverage. By the end of the book, you will be able to build RESTful web services with Django.
Online resource; title from title page (Safari, viewed February 21, 2018)
Keywords: Django (Electronic resource); Application program interfaces (Computer software); Web sites -- Design; Python (Computer program language); Interfaces de programmation d'applications; Sites Web; Conception; Python (Langage de programmation); APIs (interfaces); Computer programming; software development; Programming & scripting languages: general; Internet: general works; COMPUTERS; Web; Design; COMPUTERS; Programming Languages; Python; Web sites; Design